Análise constitucional das hipóteses de dedução da base de cálculo do imposto de renda das pessoas físicas - Pinto, André Luís Ulrich (2021)
The present research had as methodological approach the analysis of hypotheses of deduction of the tax base of personal income tax and its importance for the composition of the legal norm of the income tax, delimitation that allowed, with the adoption of the method proposed by the School of Logical-Semantic Constructivism, the analysis of the subordination and coordination relationships of this personal income tax legal norm with other legal norms belonging to the Brazilian positive law system, in particular, the constitutional principles of equality and hability to pay principle, protection of the minimum necessary for a decent life and the rule of competence of the referred tax.Thus, from the identification of the constitutional concept of "income and earnings of any nature", understood as types of equity increase, it was possible to understand the function of the deduction hypotheses of the personal income tax base, which are intended to adjust the base of calculation of the contributory capacity, with the exclusion of expenses necessary to guarantee the minimum vital of the taxpayer, their family members or dependents and guarantee of the maintenance of the income-producing source, thus allowing the calculation basis defined by law to measure the reais proportions of the fact and fairly integrate the formula used to determine the tax credit. When analyzing the tax legislation that deals with the hypotheses of deduction from the calculation basis of the personal income tax, quantitative and qualitative limits can be observed. It turns out that the lack of care on the part of the legislator in establishing these limits can cause the violation of the principles of equality or contributory capacity, allowing, in some cases, the taxation of amounts that are essential to guarantee the vital minimum and the maintenance of the income-producing source and, in other cases, the non-taxation of income received in amounts above those necessary to guarantee these purposes and which, for this reason, reveal the taxpayer's ability to contribute.This circumstance violates the principle of equality, as it allows taxpayers with greater economic capacity to acquire goods or contract private services, whose expenses are provided for as deductible from the personal income tax base, which may cause a regressive effect on their taxation, contrary to the criterion of the progressivity provided by the constitutional norms for its institution, since taxpayers with lower economic capacity will not have the same conditions to acquire these goods or services and, consequently, will not have the calculation of the personal income tax with a reduced calculation basis